Pemberdayaan Dasawisma Jatiarum Kota Samarinda Melalui Pemanfaatan Toga Sebagai Teh Herbal - Rahim, Abdul (Jurnal Abdi Mas Adzkia, 2023)
The Jatiarum Daswisma group, Samarinda City, East Kalimantan Province, is one vehicle used as a place to carry out KKN activities for Mulawarman University Pharmacy students since 2021, one of the work programs is the use of TOGA (Family Medicinal Plants). Because of this joint activity program, the community has succeeded in cultivating the TOGA. However, it is necessary to carry out a sustainable program so that it can increase the productivity of partner community groups through training and assistance in the development of health products based on local wisdom towards the down streaming and commercialization of products with economic value. The aim of this service program is to increase the knowledge of partner communities about the use of TOGA into economically valuable health products, improve community skills in production through training in health product development. Because of this service, the community carried out TOGA plant care activities and used the plants as herbal tea, which was carried out by women in the Rawamakmur sub-district. By holding this activity, people, especially stay-at-home parent, will know the benefits of the TOGA plant as herbal tea.